(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this paper was to provide all individuals within leadership roles with an enriched comprehension about micromanagement and the negative effects it possesses on subordinates. This objective was fulfilled by the researcher conducting investigations on numerous articles and studies conducted by other specialist in the field of supervision and management. The researcher also incorporated past experiences that were exhibited in past organizations pertaining to staff being micromanaged by different personnel in leadership roles